STRUCTURAL AND FUNCTIONAL HEART PARAMETERS IN PATIENTS WITH CHRONIC HEART FAILURE DEPENDING ON DIFFERENT BLOOD MIDDLE MASS MOLECULES LEVELS - M. A. Kondratyuk; O. M. Radchenko (Столичная издательская компания, 2015)
Aim. To identify the structural and functional heart parameters in patients with chronic heart failure (CHF) depending on severity of endogenous intoxication syndrome that is defined by blood middle mass molecules (MMM) level. Material and methods. In 110 patients with CHF standard clinical, laboratory and instrumental (echocardiography) examinations were performed. Besides the blood MMM levels were determined in all patients. The patients were divided into three groups with minimal, moderate and severe endogenous intoxication depending on MMM levels. Results. 41.8% of patients had the minimal severity of endogenous intoxication, 39.1% average degree and 19.1% severe intoxication. The patients with the highest MMM levels were specified by low left ventricular ejection fraction (p<0.05), the largest size of right ventricle, the lowest rate of preserved left ventricular function and high rate of diagnosis of increased sizes of the left atrium, interventricular septum and right ventricle. Conclusion. The MMM level can serve as a criterion for prognosis of CHF. Patients with high blood MMM level have the worst prognosis.